COMPENSATION IN NARRATIVES OF A YOUTH WITH DOWN SYNDROME: THE SINGULARITY EFFECT - DE SOUZA, FABIOLA RIBEIRO (Revista Valore, 2024)
The compensation theorization of Vygotsky’s Defectology approach introduces the idea that people with Intellectual Disabilities (ID) could reach the same social goals as those with Typical Development (TD). This theory is referenced in several studies, but little empirical evidence is presented to corroborate its thesis. Thus, it was aimed to identify evidences of this process in the narratives of a young adult with Down Syndrome (DS), in a socially valued position. Narratives were organized into units of analysis, based on the participant's positions/, highlighting central experiences, signified by speech and emotion. The results are presented in a compensatory timeline, analysed from compensation’s theorization and the Behavioural Phenotype on DS. It is concluded that the compensation is a possibility, depending on the socialization conditions. As a compensatory reaction, an epiphenomenon, named singularity effect, stands out, where ID traits seen as deficits in cross-sectional methods, in culture, are seen as qualities, facilitating inclusion and development through mediation. This study contributes with studies on compensation and DS, by means of more interpretative approaches and for the descriptions of Executive Functions in the culture. Attention is drawn to the importance of public policies for inclusion